The Effect of Adding Vinasse for Biochar Production from Bagasse by Pyrolysis Method - Eko Naryono; Susanto Susanto; Mochammad Agung Indra Iswara; Cucuk Evi Lusiani (Politeknik Negeri Malang, 2023)
The increasing industrial waste was caused problems for the environment. Bagasse is a solid waste produced from the sugar industry. Vinasse is bioethanol industry liquid waste from molasses which contains much nutrients. The vinasse and bagasse in this study was developed into biochar. This study aimed to determine the effect of vinasse addition on biochar characteristics. The yield and characteristics of the biochar were then compared. Based on gravimetric, pH, and SEM-EDX analysis, the result indicated that adding vinasse to the biochar was increasing yield, water content and ash content, lowering pH, and tend to increase nutrient levels (carbon, nitrogen, and potassium). The biochar produced from bagasse and vinasse by pyrolysis had a yield of 6.682-9.406%; water content of 7.0-8.2%; ash content of 4.8-13.6%; at pH 8.4-88; carbon content (C) of 65.07-80.88%; nitrogen (N) content of 2.06-8.66%; and potassium (K) levels of 0.00-2.15%, while phosphorus (P) levels were not detected in SEM-EDX analysis. Based on the consideration of the highest levels of nitrogen and potassium elements needed by plants, the optimum biochar was obtained from bagasse with a vinasse of 7.5%.